Legisprudence : a new theoretical approach to legislation : proceedings of the Fourth Benelux-Scandinavian Symposium on Legal Theory /: a new theoretical approach to legislation : proceedings of the Fourth Benelux-Scandinavian Symposium on Legal Theory. (2002) - Unknown
No abstract available